2021
DOI: 10.1002/pc.26232
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of nanocellulose from sugarcane bagasse and its characterization for potential applications

Abstract: The development of food packaging films from nanocellulose has received attention from researchers. In this study, the chemo-mechanical method has been used to obtain nanocellulose from sugarcane bagasse. The shape and size of the nanocellulose were examined by field emission scanning electron microscopy (FE-SEM) using ImageJ software, and the result was found to be in good agreement with that of dynamic light scattering (DLS) analysis.Various characterizations such as X-ray diffraction (XRD), Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 66 publications
9
42
0
Order By: Relevance
“…[6] Several studies have been conducted to replace glass fiber with bio/natural fibers. [7][8][9][10] However, it has declined the mechanical properties of hybrid composites. A survey by Ashish kumre [11] on sisal glass fiber reinforced polymer composites concluded that the sisal/glass fiber composite showed lower mechanical properties than the glass fiber control sample composite.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several studies have been conducted to replace glass fiber with bio/natural fibers. [7][8][9][10] However, it has declined the mechanical properties of hybrid composites. A survey by Ashish kumre [11] on sisal glass fiber reinforced polymer composites concluded that the sisal/glass fiber composite showed lower mechanical properties than the glass fiber control sample composite.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] In addition, high compatibility of starch and NC fillers increases the water resistance of the film, which is a good feature for food packaging. [ 31,32 ] Extraction of NC from natural fibers and its applications as reinforcement in starch‐based biocomposites have been studied by many researchers. Recently, cellulose nanofibers (CNF) extracted from hemp, [ 33 ] wheat straw, [ 34 ] sisal, [ 35 ] aloe vera, [ 36 ] bamboo, [ 11,37,38 ] and banana peel [ 39 ] have been used to improve the mechanical and barrier properties of the starch‐based composites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] The advanced applications of natural fibers reinforced composites are mostly used in automobile sectors such as door, instrument panels, glove boxes, seat backs, package trays, interior parts, etc. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The advanced applications of natural fibers reinforced composites are mostly used in automobile sectors such as door, instrument panels, glove boxes, seat backs, package trays, interior parts, etc. [7][8][9] Date palm fibers (DPF) represent the most interesting natural fiber especially in the Middle East and North African countries, Algeria alone has more than 18.6 million trees, [10,11] and various date palm tree residues can be obtained after cultivation and fruit harvesting such as twigs, leaf stalks, and tree trunks. These agricultural wastes can be used to develop a promising biomaterial based on DPF for reinforcing thermoplastic polymers in various applications such as packaging and automobile components.…”
Section: Introductionmentioning
confidence: 99%